Idiopathic and radiation-induced myxofibrosarcoma in the head and neck—case report and literature review - Bin Zhang (BMC, 2021)
Abstract Background Myxofibrosarcoma (MFS), especially radiation-Induced MFS (RIMFS) in the head and neck, is an extremely rare malignant fibroblastic tumor. The diagnosis and treatment of MFS remain great challenges. In the present study, we presented one case of RIMFS. Combined with previous literature, the clinical features, essentials of diagnosis, and treatment modalities of MFS in the head and neck were reviewed to better understand this rare entity. Case presentation We reported a case of RIMFS under the left occipital scalp in a 20-year-old girl with a history of medulloblastoma surgery and radiotherapy in 2006. A total tumor resection was performed with preservation of the overlying scalp the underlying bone, and no adjuvant therapy was administered after the first operation. The postoperative pathological diagnosis was high-grade MFS. The tumor relapsed 6 months later, and then, a planned extensive resection with negative surgical margins was carried out, followed by radiotherapy. No relapse occurred in a 12-month postoperative follow-up. Conclusions Planned gross total resection (GTR) with negative margins is the reasonable choice and footstone of other treatments for MFS. Ill-defined infiltrated borders and the complicated structures make it a great trouble to achieve total resection of MFS in the head and neck, so adjuvant radiotherapy and chemotherapy seem more necessary for these lesions.